2022
DOI: 10.1111/jpc.15881
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of severe neonatal hyperbilirubinaemia during social distancing

Abstract: Aim Social distancing guidelines implemented with the COVID‐19 pandemic impacted health‐care utilisation and disrupted critical social supports. Resurgence of highly transmissible strains has resulted in revisiting restrictions with potential impacts on newborn health. With concerns for inadequate post‐partum support, we sought to determine if social distancing correlated with increased rates of readmission for hyperbilirubinaemia. Methods Retrospective chart review identified all readmissions for hyperbilirub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Pandemic-specific factors may have contributed to our findings as the risk of newborn rehospitalization may have changed during this time. While some studies suggest that the frequency of overall post-discharge newborn rehospitalization did not change during the pandemic [ 28 , 29 ], there have been reports of increased rehospitalization risk in some subgroups such as those born to nulliparous mothers [ 30 ] and those readmitted for hyperbilirubinemia [ 31 ]. One nation-wide study from England found that while acute care presentations decreased by 16.7% overall during vs. before the pandemic, attendance for feeding problems and neonatal jaundice increased by 7.5% and 12.8% respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pandemic-specific factors may have contributed to our findings as the risk of newborn rehospitalization may have changed during this time. While some studies suggest that the frequency of overall post-discharge newborn rehospitalization did not change during the pandemic [ 28 , 29 ], there have been reports of increased rehospitalization risk in some subgroups such as those born to nulliparous mothers [ 30 ] and those readmitted for hyperbilirubinemia [ 31 ]. One nation-wide study from England found that while acute care presentations decreased by 16.7% overall during vs. before the pandemic, attendance for feeding problems and neonatal jaundice increased by 7.5% and 12.8% respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This defect results from structural malformation or altered elasticity of the ligaments that normally fix the spleen below the left dome of the diaphragm. 1 Clinical presentation is highly variable, and diagnosis may represent an incidental finding in asymptomatic patients. Nevertheless, patients may present with an acute abdomen due to splenic torsion or with chronic/intermittent abdominal pain deriving from partial torsion and spontaneous de-torsion of the spleen.…”
Section: Dear Editor Acute Abdomen Due To Torsion Of a Wandering Sple...mentioning
confidence: 99%
“…Most of the severe cases occur in low-and middle-income countries. In addition, shortened stays at maternity wards after delivery are shown to increase the risk of hospital readmission for NNJ, which was further exacerbated during the COVID-19 pandemic [16,17]. To reduce the adverse consequences of NHB, timely detection of infants with the condition is important [18].…”
Section: Introductionmentioning
confidence: 99%